(untitled) (Scientific journal of the Fergana State University, 2025)
This article discusses the spiritual and educational activities being carried out in Uzbekistan, their effectiveness, the social appearance of the population, and the state of the social and spiritual environment. It emphasizes the importance of strengthening the spiritual and educational foundations in the life of society. The issue of educating morally and physically mature youth is a national task for contemporary Uzbekistan, and the analysis highlights that the consistent and resolute continuation of efforts towards this noble goal is a key criterion in this field.